2007
DOI: 10.1002/eat.20473
|View full text |Cite
|
Sign up to set email alerts
|

Does the evidence point to a binge eating phenotype?: Comment on Gordon et al. (2007) and Wonderlich et al. (2007)

Abstract: The article by Gordon et al. 1 presents a very understandable description of taxometric analyses. These writers are to be commended for taking this complex topic and making it comprehensible to those who are not experts in the field of taxometrics and classification research. Gordon et al. 1 conclude that the results of taxometric studies suggest the existence of three diagnostic groups, bulimia nervosa, anorexia nervosa, restricting type, and binge eating disorder. They recommend conceptualizing bulimia nervo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Given the support for BED as a clinically relevant diagnosis (Javaras et al, 2008;Pope et al, 2006;Williamson, 2007;Wilson et al, 2007), one could expect a higher proportion of PDs in BED than in the clinically more heterogeneous EDNOS category (excluding BED), in which more patients are in a process of recovery compared with BED (Agras et al, 2009). However, because the levels of eating pathology and general psychopathology between EDNOS and BED have been reported comparable in a previous meta-analysis (Thomas et al, 2009), there is insufficient evidence to make any strong predictions.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Given the support for BED as a clinically relevant diagnosis (Javaras et al, 2008;Pope et al, 2006;Williamson, 2007;Wilson et al, 2007), one could expect a higher proportion of PDs in BED than in the clinically more heterogeneous EDNOS category (excluding BED), in which more patients are in a process of recovery compared with BED (Agras et al, 2009). However, because the levels of eating pathology and general psychopathology between EDNOS and BED have been reported comparable in a previous meta-analysis (Thomas et al, 2009), there is insufficient evidence to make any strong predictions.…”
mentioning
confidence: 85%
“…It is subsumed under EDNOS but is increasingly recognized as a distinct diagnostic disorder on the basis of taxometric analyses (Williamson, 2007), family aggregation studies (Javaras et al, 2008), treatment response research (Wilson et al, 2007), and studies of clinical course (Pope et al, 2006). Two extensive reviews (StriegelMoore and Franko, 2007;Wonderlich et al, 2009) also conclude positively with respect to the merit of BED as a distinct eating disorder diagnosis, and hence, it is now proposed as a separate ED diagnosis in the DSM-5 (APA, 2012).…”
mentioning
confidence: 99%
“…Different studies supported the variability in the phenomenology of binge eating associated with BN and BED syndromes [2,9,10,11,12]. The feelings and the affects experienced during binge episodes seem to be different in BN and BED, with less prebinge emotional activation in BED [13], and it has been suggested that the association between impulsivity, eating psychopathology and different emotions with binge eating plays different roles in BN and BED [14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Objective binge eating is characterized by the consumption of a large amount of food and a sense of loss of control, whereas a subjective binge involves the same sense of loss of control but the consumption of a small to moderate amount of food. It has been observed that a person’s definition of ‘large amount’ is highly subjective and influenced by personal beliefs and rules, which can vary from day to day, and that subjective binges are often associated with significant eating disorder psychopathology and clinical impairment, similar to objective binges [4,5,6,7,8,9]. …”
Section: Introductionmentioning
confidence: 99%